2014
DOI: 10.1093/aob/mcu007
|View full text |Cite
|
Sign up to set email alerts
|

Floral display size, conspecific density and florivory affect fruit set in natural populations of Phlox hirsuta, an endangered species

Abstract: The results indicate that seed production in P. hirsuta can be maximized by selectively augmenting populations in areas containing isolated large plants, by reducing the population sizes of florivorous beetles and by excluding mammals that consume unripe fruits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 86 publications
1
31
0
Order By: Relevance
“…This was also reported in several other alpine plant species that suffered critical pollen limitation (e.g., Ranunculus acris L., Totland, 1994; Chaetanthera euphrasioides F. Meigen, Arroyo et al, 2006). In addition, the increase in synchronous blooming flowers within an inflorescence in high altitude populations formed a larger floral display, which may be beneficial for attracting pollinators (Benitez-Vieyra et al, 2006;Ruane et al, 2014). In P. siphonantha, corolla tube length decreased in higher altitudes compared to lower altitudes.…”
Section: Plasticity In Floral Traits and Mating Systemsupporting
confidence: 69%
See 1 more Smart Citation
“…This was also reported in several other alpine plant species that suffered critical pollen limitation (e.g., Ranunculus acris L., Totland, 1994; Chaetanthera euphrasioides F. Meigen, Arroyo et al, 2006). In addition, the increase in synchronous blooming flowers within an inflorescence in high altitude populations formed a larger floral display, which may be beneficial for attracting pollinators (Benitez-Vieyra et al, 2006;Ruane et al, 2014). In P. siphonantha, corolla tube length decreased in higher altitudes compared to lower altitudes.…”
Section: Plasticity In Floral Traits and Mating Systemsupporting
confidence: 69%
“…Variations in mating system among populations should be attributed to the changes in pollination environments. In addition, the increase in synchronous blooming flowers within an inflorescence in high altitude populations formed a larger floral display, which may be beneficial for attracting pollinators (Benitez-Vieyra et al, 2006;Ruane et al, 2014). Our study revealed that plasticity in floral traits was adaptive in response to changes of pollination conditions as well as the mating system in P. siphonantha.…”
Section: Plasticity In Floral Traits and Mating Systemmentioning
confidence: 62%
“…Plot density and floral display size interacted to influence fruit set. In other studies, the effect of local density of conspecifics on pollinator visitation (Grindeland et al 2005, Jing et al 2013, Weber and Kolb 2013 and fruit set (Ruane et al 2014, Henneresse et al 2017 has also been reported to be contingent upon floral display size. According to the results of Henneresse et al (2017), we expected fruit set to be positively correlated with floral display size in lowdensity plots.…”
Section: Fruit Set and Pollinator Abundance And Behaviourmentioning
confidence: 85%
“…In accordance to our expectations, the overall incidence of antagonists mostly reduced female fitness in relation to pollinators. The negative effects of florivores and nectar-robbers on female fitness components have been broadly reported (e.g., Schemske & Horvitz 1988, Irwin & Brody 1998, Castro et al 2008, Ruane et al 2014, Irwin et al 2015. Otherwise, it would be interesting to discern direct from indirect effects of floral antagonists, especially by nectar-robbers, on reproductive…”
Section: Discussionmentioning
confidence: 99%
“…producing holes in flowers to remove nectar (Inouye 1980, Irwin et al 2001. Increased attractiveness to pollinators by means of a higher number or size of flowers displayed intensifies florivore (Galen 1999, Teixido et al 2011, Ruane et al 2014 and nectarrobber incidence (Irwin & Brody 1998, Irwin 2006, Lobo et al 2016. The total outcome of nectar-robbers and florivores, including direct and indirect effects (respectively, damage to floral reproductive organs and changes in pollination derived from decreasing attractiveness or nectar availability) can strongly affect plant fitness by reducing reproductive output (e.g., Schemske & Horvitz 1988, Irwin et al 2001, Castro et al 2008, Carper et al 2016.…”
mentioning
confidence: 99%